Physical aspects and streamline analysis on hydromagnetic nonlinear radiative flow of Carreau-Yasuda fluid. (21st December 2020) - Hari Babu, B; Rao, P Srinivasa; Reddy, M Gnaneswara
Abstract: The physical aspects of flow and heat transport analysis of non-Newtonian (Carreau-Yasuda) fluid through an upper paraboloid surface of revolution has been scrutinized. Non-linear radiation, magnetic field, heat generation are considered in this study. The governing flow equations are modeled in the formulation. The governing flow equations (PDE's) are changed into a system of ODE's by employing the related transformation variables. The highly non-linear and coupled ODE's are resolved aid of Runge–Kutta fourth-order along shooting numerical procedure. The physical flow and temperature phenomena have analyzed for both Newtonian and Non-Newtonian fluid cases through plots for the dimensionless sundry variables. The fluid velocity dwindled with the escalation of the magnetic field. An increase in fluid temperature is observed against the temperature ratio variable. Behaviour of fluid temperature of Newtonian fluid is excessive as compared to the Carreau-Yasuda fluid case for the exponential parameter N . The present model (Carreau-Yasuda fluid) is simplified to the viscous fluid (Newtonian fluid) case when n  = 1. The streamline flow patterns are reduced for higher thermal Grashof number Gr . The numerical comparison has been deliberated with existing outcomes for a limit case. The heat augmentation analysis through Carreau-Yasuda liquid has prominent applications in non-linear science and industrial technology.